Characterized the Adipogenic Capacity of Adipose-Derived Stem Cell, Extracellular Matrix, and Microenvironment With Fat Components Grafting - Jiang, Wenqing; Cai, Junrong; Guan, Jingyan; Liao, Yunjun; Lu, Feng; Ma, Jingjing; Gao, Jianhua; Zhang, Yuteng (Frontiers in Cell and Developmental Biology, 2021)
Background: Autologous fat grafting has been a widely used technique; however, the role of adipose-derived stem cells (ASCs), extracellular matrix (ECM), and microenvironment in fat regeneration are not fully understood. Methods: Lipoaspirates were obtained and processed by inter-syringe shifting to remove adipocytes, yielding an adipocyte-free fat (Aff). Aff was then exposed to lethal dose of radiation to obtain decellularized fat (Df). To further remove microenvironment, Df was rinsed with phosphate-buffered saline (PBS) yielding rinsed decellularized fat (Rdf). Green fluorescent protein (GFP) lentivirus (LV-GFP)-transfected ASCs were added to Df to generate cell-recombinant decellularized fat (Crdf). Grafts were transplanted subcutaneously into nude mice and harvested over 3 months. Results: Removal of adipocytes (Aff) didn’t compromise the retention of fat grafts, while additional removal of stromal vascular fraction (SVF) cells (Df) and microenvironment (Rdf) resulted in poor retention by day 90. (Aff, 82 ± 7.1% vs. Df, 28 ± 6.3%; p < 0.05; vs. Rdf, 5 ± 1.2%; p < 0.05). Addition of ASCs to Df (Crdf) partially restored its regenerative potential. Aff and Crdf exhibited rapid angiogenesis and M2-polarized macrophages infiltration, in contrast to impaired angiogenesis and M1-polarized inflammatory pattern in Df. GFP+ ASCs participated in angiogenesis and displayed a phenotype of endothelial cells in Crdf. Conclusion: Adipose ECM and microenvironment have a weak capacity to stimulate in vivo adipogenesis while ECM alone cannot induce adipogenesis. ASCs were the important cellular component that developed into vessels and regulated macrophage polarization leading to mature adipogenesis.